Potential Prognostic Indicators for Patients With Retinal Vein Occlusion - Yin, Shan; Cui, Yanyan; Jiao, Wanzhen; Zhao, Bojun (Frontiers in Medicine, 2022)
The second most prevalent cause of retinal vascular disease is retinal vein occlusion (RVO). RVO raises intravascular pressure in capillary and veins, triggering vessel barrier collapse and subsequent leaking of blood or plasma components into tissue (edema). Macular edema (ME) is a major complication of RVO that results in significant visual impairment. Laser therapy, intravitreal steroid injections, and vascular endothelial growth factor (VEGF) inhibitors are the major therapeutic techniques. Different therapies reduce ME of RVO and improve visual activity. However, some people have no impact on the resolution of macular edema, while others have a poor visual prognosis despite full ME cure. There are many investigators studied the relationship between indicators of various instruments with visual activity. However, a summary of those findings is currently lacking. Therefore, we will focus on the predictive factors of different studies associated with positive VA outcomes, which would be very useful and important to help address both treatment expectations and methods for RVO patients.